Respuesta :
Answer: [tex]j=-25[/tex]
Step-by-step explanation:
Given the equation [tex]\frac{j}{5}+1=-4[/tex], you need to:
Apply the Subtraction property of equality and subtract 1 from both sides of the equation:
[tex]\frac{j}{5}+1-(1)=-4-(1)[/tex]
[tex]\frac{j}{5}=-5[/tex]
Now, apply the Multiplication property of equality and mutiply both sides of the equation by 5:
[tex](5)(\frac{j}{5})=(-5)(5)[/tex]
Therefore, the solution of this equation is:
[tex]j=-25[/tex]
Answer:-25
Step-by-step explanation:
(j)/5+1=-4 - subtract 1 from both sides
(j)/5= -5 - multiply both sides by 5
j = -25 - plug -25 back in to check your answer.